Myoepithelioma-like Tumors of the Vulvar Region: A Distinctive Group of SMARCB1-deficient Neoplasms. (August 2015) - Yoshida, Akihiko; Yoshida, Hiroshi; Yoshida, Masayuki; Mori, Taisuke; Kobayashi, Eisuke; Tanzawa, Yoshikazu; Yasugi, Toshiharu; Kawana, Kei; Ishikawa, Mitsuya; Sugiura, Hitoshi; Maeda, Daichi; Fukayama, Masashi; et al.
Abstract : We describe 9 tumors that resemble soft tissue myoepitheliomas but possess certain traits that do not fit perfectly into this category. These tumors, herein referred to as "myoepithelioma-like tumors of the vulvar region, " occurred in the subcutis of the vulva and surrounding regions of adult women aged 24 to 65 years. Histologically, the tumors measured 2 to 7.7 cm and were well circumscribed, focally encapsulated, and lobulated. Tumor cells had an epithelioid to spindled shape, with fine amphophilic cytoplasm, and uniform nuclei with vesicular chromatin and nucleoli. The tumor stroma was relatively hypervascular, and comprised a mixture of myxoid and nonmyxoid components. Myxoid areas accounted for <5% to 95% of the tumor volume, wherein cells proliferated singly or in a loosely cohesive manner. In nonmyxoid areas, tumors cells grew in diffuse sheets or storiform arrangements. Immunohistochemically, all tested tumors were positive for vimentin, epithelial membrane antigen, and estrogen receptor; most tumors expressed actin. All tumors were negative for S100 protein, glial fibrillary acidic protein, and CD34. Cytokeratin expression was absent in all but 2 tumors, which showed rare positivity. SMARCB1 expression was deficient in all cases. EWSR1, FUS, and NR4A3 rearrangements were absent. All tumors were treated through surgery. Although 3 tumors regrew or recurred after intralesional excision, all 9 patients were alive without metastases at a mean follow-up of 66 months. Myoepithelioma-like tumors of the vulvar region constitute a distinct group of tumors, although future research is required to determine whether they are an unusual subtype of soft tissue myoepitheliomas or a separate disease. Abstract : Supplemental Digital Content is available in the text.